Wave propagation characterization of 2D composite chiral lattice structures with circular plate inclusions. (1st August 2022) - Ruan, Haifeng; Hou, Jiahong; Li, Dong
Highlights: All the analysis process are completed by self-programming. The influences of structure on bandgap characteristics are analyzed in detail. An optimized chair lattice structure of low frequency bandgap is proposed. The vibration experiments are carried out to verify the existence of band gap. Abstract: In this work, an innovative 2D composite chiral lattice hierarchical structure containing circular plate inclusions is proposed. The circular plate inclusion is incorporated into the chiral unit cell by introducing four ligaments that connect the circular plate rim on one end and the interior edge of the ring of the chiral unit cell on the other end. The propagation wave behaviors of the chiral lattice structures are discussed by a self-developed program based on the finite element method and Bloch theorem. The effects of the ligament number of the chiral unit cell structure, the connection mode, the rotation angle of connecting rod and the size of the circular plate inclusions on the distributions of band gaps are studied. The iso -frequency contours, group velocities and phase velocities are calculated for analyzing the wave propagation. The low amplitude elastic wave transmission tests are carried out to verify the existence of band gap. Results show that the composite chiral lattice structures of anticlockwise tangential connection mode have the widest first band gap when the radius of inclusion is 32 mm. The introduction of circular plate inclusion expands the band gap-occupied regions, yet do not increase the number of band gaps. The opening frequency of the first band gap gradually decreases with an increasing inclusion size, and the width of the first band gap becomes twice as wide as that of the structure without inclusions when the circular plate inclusion occupies 80% of the ring area. These findings can provide new ideas for the design of vibration-damping metamaterials.